Dust from mining area and proposal of dust emission factors - Jia, Qi (Luleå tekniska universitet, Geoteknologi, 2011)
Mining generates great deal of particulate matter, especially for surface mining. The principle of dust generation is based on the theory of soil wind erosion. This thesis theoretically and experimentally dealt with mining dust. In chapter 1 the development of study on soil erosion by wind and mining dust were introduced. Chapter 2 elaborated the process of soil wind erosion. Soil motion during wind erosion is classified into three categories which are creeping, saltation and suspension. Threshold wind velocity, which initiates particle motion, depends on particle size, soil moisture, roughness element etc. Roughness element refers to non erodible fraction in a soil. A test on erodible fraction was included in this research.Chapter 3 presented effects and sources of mining dust. Sources include haul road, stockpiles, open surfaces, overburden removal etc. Malmberget mine operated by LKAB is one of the most important iron mines in Sweden. The mining area includes an area with huge open pit and current industrial center area. Both areas are surrounded by residential areas where people are suffering from dust problem. In this research the collected dust from 26 measuring stations during the time period Aug. 2009 to Aug. 2010 were used to calculate the dust fallout and distribution using surfer 9.0 software. It was concluded that two sources for dust generation were spotted. One was located close to the open pit, and the other was located nearby the current mining industrial center. It should be mentioned that the concentration of dust was varying with time. The maximum value happened on May in 2010. The value suddenly became extremely high compared with the other months. This was attributed to a road construction at that time. Analysis results have shown dust production around Malmberget mine was attributed to three reasons: wind erosion of the exposed area closed to the open pit, trucks transportation on haul roads, and wind erosion of stockpiles. Since the mining activities were relatively going at a constant ...